Much ado about nothing: the Italian Geological Survey, 1861-2006 - Corsi, P (History of the Earth Sciences Society, 2007)
Established on 12 December 1861, soon after the proclamation of the Kingdom of Italy in January 1861, the Geological Survey of the peninsula enjoyed a remarkably difficult life, and achieved remarkably little. Since its inception, the rivalry between academic geologists and the engineers of the Royal Mining Corps acting as field surveyors did much to alienate political and public opinion support. Underfunded and understaffed, the Survey faced periodical crisis and periodical reforms. On at least four occasions (1861, 1873, the early 1920s and 1960), the help of influential politicians concerned with the lack of a functioning State Survey, or with the very slow pace of publication of the geological map of the country, produced beneficial effects and brisk activity. This never lasted longer than a few years. In the last four decades of the twentieth century, the growth of the politically powerful community of geophysicists and the lack of political initiative and Parliamentary supervision further marginalized the Geological Survey, up to its relegation to a subordinate role within the State Agency for the Protection of the Environment.